Model Manajemen Sarana dan Prasarana dalam Pelayanan Pendidikan - Muhammad Usef Saefullah; Amin Haedari; Labisal Qolbi (Eduprof : Islamic Education Journal, 2019)
Special service management is carried out to support the success of the teaching and learning process. The success of the teaching and learning process requires good facilities for teachers as well as facilities and infrastructure to achieve it. The purpose of this study was to determine the planning, organizing, implementing, monitoring and evaluating the quality management of education services at SMAN 1 Astanajapura. This study uses a qualitative approach that is used, namely descriptive qualitative research with a case study approach. Data collection techniques are the most important step in research because the main objectives of research are observation, interviews and documentation. Activities carried out in data analysis are data reduction, data presentation, and data verification. The results of this study are for school planning to plan the availability of facilities and infrastructure for 8 years from 2016-2023. School organization and supervision is supported by competent education personnel in each subject, administrative staff who are able to work well, coordination of school principals with good school members, school committees that support the process of school activities, communities who are able to work together, good school guarding from security and the local police. The implementation that is implemented is with PAKEM learning media, optimal service in terms of administration, creative and innovative teachers, extracurricular activities, religious activities, academic and non-academic competitions, quality of graduates, in collaboration with several companies and universities. Evaluation Every year the school holds a meeting with parents of students, at the beginning of each semester a meeting with school residents to promote and evaluate quality management in educational services. Abstrak Manajemen pelayanan khusus dilakukan untuk mendukung keberhasilan proses belajar mengajar. Keberhasilan proses belajar mengajar membutuhkan fasilitas baik pengajar maupun sarana dan prasarana untuk mencapainya. Tujuan dari penelitian ini untuk mengetahui perencanaan, pengorganisasian, pelaksanaan, pengawasan dan evaluasi menajemen mutu pelayanan pendidikan di SMAN 1 Astanajapura. Penelitian ini menggunakan pendekatan kualitatif yang digunakan yaitu penelitian kualitatif deskriptif dengan pendekatan studi kasus (case study). Teknik pengumpulan data merupakan langkah yang paling utama dalam penelitian karena tujuan utama dari penelitan adalah obsevasi, wawancara dan dokumentasi. Kegiatan yang dilakukan dalam analisis data yaitu reduksi data, penyajian data, dan verifikasi data. Hasil penelitian ini ntuk perencanaan sekolah merencanakan tersedianya sarana dan prasarana selama 8 tahun dari mulai 2016-2023. Pengorganisasian dan pengawasan sekolah didukung dari tenaga pendidikan yang berkompeten disetiap mata pelajarannya, staf administrasi yang mampu bekerja dengan baik, koordinasi kepala sekolah dengan warga sekolah yang baik, komite sekolah yang mendukung proses kegiatan sekolah, masyarakat yang mampu bekerja sama, penjagaan sekolah baik dari security dan polisi setempat. Pelaksanaan yang diterapkan yaitu dengan media pembelajaran PAKEM, pelayanan yang optimal dari segi adminstrasi, guru yang kreatif dan inovaif, kegiatan ekstrakulikuler, kegiatan keagamaan, perlombaan akademik, maupun non akademik, mutu lulusan, bekerja sama dengan beberapa perusahaan dan perguruan tinggi. Evaluasi setiap tahun sekolah mengadakan rapat dengan dengan orang tua murid, setiap awal semester rapat dengan warga sekolah untuk memajukan dan mengevaluasi manajemen mutu dalam pelayanan pendidikan.